Three Horizons of Technical Skills in Artificial Intelligence for the Sustainability of Insurance Companies - (:unkn) unknown (MDPI, 2024)
Insurance companies are experiencing unprecedented growth due to several emerging technology functionalities that have transformed the industry’s operations. Through the Three Horizons framework, this study explores the technical skills required to use...
Keywords: Inteligencia artificial; Seguros